2019
DOI: 10.3727/096504018x15442985680348
|View full text |Cite
|
Sign up to set email alerts
|

PAR2 Inhibition Enhanced the Sensitivity of Colorectal Cancer Cells to 5-FU and Reduced EMT Signaling

Abstract: The aim of this study was to investigate the underlying mechanisms that transforming growth factor-β (TGF-β)-mediated epithelial-to-mesenchymal transition (EMT) in tumor cells contributes to 5-FU resistance. A series of experiments involving cell viability and caspase activity analyses, siRNA transfection, RNA isolation, and quantitative-PCR (qPCR) assay, cell migration analysis, Western blotting analysis of total protein and membrane protein were performed in this study. Mouse xenograft model was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Romano et al found that 5-FU activated TGF-β pathway and the transcription of ACVRL1, FN1 and TGFB1 in drug resistant colorectal carcinoma cells [11]. In line with our results, a recent publication showed that PAI-1 expression was elevated in CRC tissue biopsies after 5-FU chemotherapy administration [40]. Also, Robinson et al showed increased expression of PAI-1 in the liver of tumor-bearing FOLFOX-treated mice in comparison to vehicle treated control mice [41].…”
Section: Discussionsupporting
confidence: 92%
“…Romano et al found that 5-FU activated TGF-β pathway and the transcription of ACVRL1, FN1 and TGFB1 in drug resistant colorectal carcinoma cells [11]. In line with our results, a recent publication showed that PAI-1 expression was elevated in CRC tissue biopsies after 5-FU chemotherapy administration [40]. Also, Robinson et al showed increased expression of PAI-1 in the liver of tumor-bearing FOLFOX-treated mice in comparison to vehicle treated control mice [41].…”
Section: Discussionsupporting
confidence: 92%
“…44 Inhibition of PAR2 suppresses EMT and promotes the chemo-resistance of CRC to 5-FU. 45 Previous study showed that AQP5 silencing has an anti-cancer effect via regulating Wnt/β-catenin pathway and EMT progress, 46,47 which is consistent with our research. Additionally, AQP5 promotes hepatocellular carcinoma metastasis via modulating NF-κB-regulated EMT progress.…”
Section: Discussionsupporting
confidence: 91%
“…31 Another study reported that PAR2 is involved in EMT via TGF-β signaling in colorectal cancer cells. 26 In this study, the PAR2 agonist tended to increase the expression of EMT markers, such as α-SMA and vimentin, but had no effect on TGFB expression, indicating that PAR2 may induce EMT independent of the TGF-β pathway in canine MC cells. However, this study did not examine the level of proteins associated with TGF-β activation, such as Smads.…”
Section: Discussionmentioning
confidence: 47%